2018
DOI: 10.1016/j.ymben.2017.11.011
|View full text |Cite|
|
Sign up to set email alerts
|

Post-translational regulation of metabolism in fumarate hydratase deficient cancer cells

Abstract: Deregulated signal transduction and energy metabolism are hallmarks of cancer and both play a fundamental role in tumorigenesis. While it is increasingly recognised that signalling and metabolism are highly interconnected, the underpinning mechanisms of their co-regulation are still largely unknown. Here we designed and acquired proteomics, phosphoproteomics, and metabolomics experiments in fumarate hydratase (FH) deficient cells and developed a computational modelling approach to identify putative regulatory … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…3). Gonçalves et al reported that pyruvate dehydrogenase activity was inhibited through its phosphorylation in UOK262 cells 10 , which is consistent with the results observed in this study (Fig. 3).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…3). Gonçalves et al reported that pyruvate dehydrogenase activity was inhibited through its phosphorylation in UOK262 cells 10 , which is consistent with the results observed in this study (Fig. 3).…”
Section: Discussionsupporting
confidence: 93%
“…Via metabolome analysis, Adam et al and Zheng et al revealed that FH inactivation altered urea cycle metabolism and caused arginine auxotrophy 8 , 9 . In addition, Gonçalves et al demonstrated the increased phosphorylation of pyruvate dehydrogenase and restriction of carbon entry from glucose to the TCA cycle in FH-deficient cells by phosphoproteome analysis and 13 C tracer analysis 10 . As described above, how FH defect modulates cellular energy metabolism has been addressed by various approaches.…”
Section: Introductionmentioning
confidence: 99%
“…First, as often observed in mitochondrial diseases, FH-deficient cells increase their glycolytic rates and instead of oxidising glucose in the mitochondria they shunt it into lactate production [34] and other glycolytic branches, including the pentose phosphate pathway (PPP) [35]. Interestingly, as will be detailed in section 3.2.2, this glycolytic shift is supported by a transcriptional reprogramming of glycolytic enzymes and the inhibition of pyruvate dehydrogenase (PDH), which in turn blocks the entry of glucose into the mitochondria [36] (Fig. 2 and Fig.…”
Section: Fh Loss Induces a Multi-layer Cellular Reprogramming That Leads To Transformation 31 Metabolic Rewiring In Fh-deficient Cellsmentioning
confidence: 99%
“…In fact, since these networks are built based on genomic information they may contain false positive reactions (reactions which should not be included) and false negatives (missing reactions). Recon2 is a highly curated reconstruction for the human metabolic network applied in many studies, but improved versions are regularly released, such as Recon3D, which has been recently introduced but has still not been used in the field of metabolomics ( 59 62 ). The other challenge is the algorithm choice to extract sub-networks.…”
Section: Discussionmentioning
confidence: 99%